2008
DOI: 10.1007/s00425-008-0719-z
|View full text |Cite
|
Sign up to set email alerts
|

Pepper pectin methylesterase inhibitor protein CaPMEI1 is required for antifungal activity, basal disease resistance and abiotic stress tolerance

Abstract: Pectin is one of the main components of the plant cell wall that functions as the primary barrier against pathogens. Among the extracellular pectinolytic enzymes, pectin methylesterase (PME) demethylesteriWes pectin, which is secreted into the cell wall in a highly methylesteriWed form. Here, we isolated and functionally characterized the pepper (Capsicum annuum L.) gene CaPMEI1, which encodes a pectin methylesterase inhibitor protein (PMEI), in pepper leaves infected by Xanthomonas campestris pv. vesicatoria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
141
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(148 citation statements)
references
References 93 publications
7
141
0
Order By: Relevance
“…This technology, unlike that involving PGs, is readily available for application purposes, because plants overexpressing PMEI have a normal growth and, in the case of Arabidopsis, even exhibit an increased biomass. Furthermore, since plants overexpressing PMEI display a higher resistance to microbial pathogens (13,23), crops with increased HGA methyl-esterification may also possess this additional desirable trait. Independently of the kind of genes that are used, we have shown that a reduction of the acidic HGA content ultimately determines an increased cell wall susceptibility to hydrolytic degradation.…”
Section: Resultsmentioning
confidence: 99%
“…This technology, unlike that involving PGs, is readily available for application purposes, because plants overexpressing PMEI have a normal growth and, in the case of Arabidopsis, even exhibit an increased biomass. Furthermore, since plants overexpressing PMEI display a higher resistance to microbial pathogens (13,23), crops with increased HGA methyl-esterification may also possess this additional desirable trait. Independently of the kind of genes that are used, we have shown that a reduction of the acidic HGA content ultimately determines an increased cell wall susceptibility to hydrolytic degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Cell wall modifications can provide an increased physical barrier against potential pathogens, while improving tolerance to drought and oxidative stress and maintaining turgor during osmotic stress (Piro et al, 2003;Pelloux et al, 2007;An et al, 2008;Leucci et al, 2008). The observed up-regulation of cell wall modification proteins in response to combined nematode and dehydration stress may therefore be a general defensive mechanism activated to confer broad-spectrum tolerance against multiple stresses.…”
Section: Cell Wall Modificationmentioning
confidence: 99%
“…For example, overexpression of pepper CaPMEI1 in Arabidopsis improved plant resistance to P. syringae possibly due to the antimicrobial activity of the protein and the activation of the salicylic acid pathway, although a possible contribution of altered cell wall esterification has not been excluded. 52 Moreover, CaPMEI overexpressing plants exhibited higher drought and oxidative stress tolerance. 52 Pectin acetylation can also affect plant resistance against invading pathogens.…”
Section: Post-synthetic Modifications Of the Cell Wall Affect Cwi Andmentioning
confidence: 99%
“…52 Moreover, CaPMEI overexpressing plants exhibited higher drought and oxidative stress tolerance. 52 Pectin acetylation can also affect plant resistance against invading pathogens. Recent work demonstrated that reduction of pectin acetylation increased Arabidopsis resistance to microbial pathogens.…”
Section: Post-synthetic Modifications Of the Cell Wall Affect Cwi Andmentioning
confidence: 99%
See 1 more Smart Citation